PURIFICATION OF TOMATO BUSHY STUNT VIRUS PARTICLES BY ONE-STEP HYDROXYAPATITE COLUMN CHROMATOGRAPHY - Tleukulova, Zh.; Stamgaliyeva, Z.; Dildabek, A.; Mukiyanova, G.; Omarov, R.T. (EURASIAN CHEMICO-TECHNOLOGICAL JOURNAL, 2021)
The main aim of this work was to develop a time-saving and cost-effective purification method of infectious plant viral nanoparticles. Virions of Tomato bushy stunt virus (TBSV), which is a member of Tombusvirus genus, were purified by one-step Biogel HT Hydroxyapatite (HA) column chromatography. Extracts from Nicotiana benthamiana plants infected with TBSV were directly loaded onto the HA column and eluted by 10 mM sodium phosphate buffer (pH 6.8). A specificity of virions has been confirmed by immunoblotting and electron microscopy. Homogeneity of virions was tested by SDS-PAGE, where only 41 kDa polypeptide bands referring to the capsid protein of TBSV were detected by Coomassie staining. The biological infectious activity of a purified material was demonstrated by observing TBSVspecific symptoms observed in N. benthamiana plants at 7‒10 days of postinoculation (dpi). Moreover, purified virions were used for immunization of the BALb/c mouse to raise primary antibodies against the TBSV virus. Our results show that in low concentrations of sodium phosphate buffer total proteins extracted from infected plants adsorb to HA sorbent, while viral particles do not adsorb to the HA matrix and flow throw column due to Ca2+ ions implicated in TBSV virions’ structure. This highly effective and simple virus purification protocol can also be used for the isolation of other plant virions.
Keywords: Type of access: Open Access; Virus particles; Tomato bushy stunt virus; Purification; Hydroxyapatite column chromatography